MILLER FISHER SYNDROME: A RARE BENIGN VARIANT OF GUILLAIN- BARRE SYNDROME: Poster Presentation - Case Report - General practitioner - Ayu Anggraini Kusumaningrum; Zahira Rikiandraswida; Riski Prihatningtias (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Guillain-Barré Syndrome (GBS) is a broad category of syndromes that includes several types of acute immune-mediated polyneuropathy. Miller Fisher Syndrome (MFS) is a scarce variant of GBS (1-2:1,000,000) that presents at least 2 of ataxia, areflexia, and ophthalmoplegia. Case Illustration : A 32 years-old-man came to JEC-Candi with ophthalmic discomfort and exhibited a week onset of total ophthalmoplegia, ptosis, diplopia, and lagophthalmos. Two weeks backward, the patient had a respiratory infection then emerged symmetrical sensory abnormalities (glove-and-stocking-type pinprick sensations in distal extremities). Neurological examinations were performed, and the patient got multiple cranial nerve weaknesses (oculomotor, trochlear, abducens, trigeminal, and facial) both in motoric and sensory, ataxia (positive Romberg sign, stepping test, gait, shallow-knee- bend), and negative pathologic reflexes. Hematology showed leukocytosis, MRI and CT-Scan were normal. Pulse therapy was given (Methylprednisolone 1g/day) for three days, neuroprotector and artificial tears added. Ataxia and diplopia improved, then the patient was referred to Kariadi Hospital for five-times plasmapheresis that involved neurologist and internist. Ophthalmoplegia improved slowly, and lagophthalmos disappeared one month after hospital admission. Discussion : GBS subvariant could overlap; this case presents bifacial weakness with paresthesia and MFS. Viral infection precedes neurological symptoms in most cases, with an average of 10 days of the incubation period. Ataxia, diplopia, and ophthalmoplegia may confuse the physician and presume an upper motor neuron sign or central cause. Steroid and plasmapheresis evince meaningful upturn. Conclusion : This rare disease requires a multidisciplinary approach to cure and diagnose. Nonetheless, MFS has a good prognosis. Appropriate treatment selection will enhance patients' quality of life.